Pengaruh Beban Kerja dan Self Efficacy terhadap Kinerja Tenaga Kesehatan Puskesmas Bola Kecamatan Bola Kabupaten Sikka - Marianus Ronal Dita; Walter Obon; Viktor Eko Transilvanus (Program Studi Kewirausahaan Universitas Nusa Nipa Indonesia, 2024)
This study aims to: (1) describe the workload, self-efficacy and performance of health workers at the Bola Health Center, Bola District, Sikka Regency; (2) analyzing the effect of workload and self-efficacy on the performance of health workers at the Bola District Health Center, Bola District, Sikka Regency, both partially and simultaneously. The population in this study was the health workers at the Bola Health Center, Bola District, Sikka Regency, totaling 50 people. Because the population is limited, this research was carried out by census or saturated sampling. Data were collected through questionnaires and analyzed using descriptive methods and inferential statistics, namely multiple linear regression, and hypothesis testing was carried out through F and t tests. The results of the descriptive analysis show that the variables of health worker performance, workload and self-efficacy are categorized as quite good. The results of the t-test statistic show that partially the workload variable has no significant effect on the health worker performance variable, the self-efficacy variable has a significant effect on the health worker performance variable. The results of the F test statistic show that simultaneously the workload and self-efficacy variables have a significant effect on the performance of health workers. The results of the determination analysis showed that the two independent variables in this study were able to explain the variations in the ups and downs of the performance of health workers at the Bola Health Center, Bola District, Sikka Regency, amounting to: 86.2%.